Exercise in neuromuscular disease. Issue 1 (22nd May 2013) - Anziska, Yaacov; Sternberg, Alex
ABSTRACT In this review, we present an overview of the role of exercise in neuromuscular disease (NMD). We demonstrate that despite the different pathologies in NMDs, exercise is beneficial, whether aerobic/endurance or strength/resistive training, and we explore whether this benefit has a similar mechanism to that of healthy subjects. We discuss further areas for study, incorporating imaginative and novel approaches to training and its assessment in NMD. We conclude by suggesting ways to improve future trials by avoiding previous methodological flaws and drawbacks in this field. Muscle Nerve, 2013